2019
DOI: 10.1093/mnras/stz2840
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the metallicity-specific star formation history on double compact object mergers

Abstract: We investigate the impact of uncertainty in the metallicity-specific star formation rate over cosmic time on predictions of the rates and masses of double compact object mergers observable through gravitational waves. We find that this uncertainty can change the predicted detectable merger rate by more than an order of magnitude, comparable to contributions from uncertain physical assumptions regarding binary evolution, such as mass transfer efficiency or supernova kicks. We statistically compare the results p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
413
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(458 citation statements)
references
References 125 publications
43
413
2
Order By: Relevance
“…Stevenson et al 2017;Barrett et al 2018;Stevenson et al 2019;Bavera et al 2019) or a NS (e.g. Vigna-Gómez et al 2018;Neijssel et al 2019;Broekgaarden et al 2019), but did not follow any subsequent evolution of these objects. To analyse whether a NS is also a pulsar, other properties such as the magnetic field and spin period need to assigned to the NS and calculated over time, e.g.…”
Section: Modelling Pulsar Evolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stevenson et al 2017;Barrett et al 2018;Stevenson et al 2019;Bavera et al 2019) or a NS (e.g. Vigna-Gómez et al 2018;Neijssel et al 2019;Broekgaarden et al 2019), but did not follow any subsequent evolution of these objects. To analyse whether a NS is also a pulsar, other properties such as the magnetic field and spin period need to assigned to the NS and calculated over time, e.g.…”
Section: Modelling Pulsar Evolutionmentioning
confidence: 97%
“…The metallicity is kept constant across all models to solar metallicity, Z = 0.0142 (Asplund et al 2009), which is a justified assumption since we focus on Milky Way field DNS systems. Additionally Neijssel et al (2019) showed that Table 2. Description of models used in this paper.…”
Section: Radio Populationmentioning
confidence: 99%
“…Therefore, even if it is possible to determine the host galaxy despite the limited spatial localization of binary BH mergers, the local observed population of stars may have formed later and hence have a different metallicity to that of the BH progenitor. This complicates estimating the rate of BH formation (Portegies Zwart & McMillan 2000;Dominik et al 2012;Abbott et al 2016b), since this estimate requires knowing the star formation rate and metallicity evolution of the universe (Madau & Dickinson 2014;Mapelli et al 2019;Neijssel et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we predict the detection rate, distribution of source parameters (eccentricity, signal-to-noise ratio, distance), and uncertainty in source parameters (eccentricity uncertainty, sky-localisation accuracy, chirp mass uncertainty) of DNSs in the Milky Way (MW) and in nearby galaxies. We generate a population of synthetic DNSs using the Compact Object Mergers: Population Astrophysics and Statistics (COMPAS) suite (Stevenson et al 2017;Barrett et al 2018;Neijssel et al 2019), and follow the evolution of these DNSs through the LISA band driven by gravitational radiation reaction, for which we use the leading quadrupole order expressions (Peters 1964). Starting from an initial population of zero-age main sequence (ZAMS) binary stars, COMPAS performs single-star evolution using the fitting formulae in Hurley et al (2000) and calculates changes in stellar and orbital properties due to wind-driven mass loss, mass transfer, common-envelope events, and SNe, until the formation of a DCO.…”
Section: Introductionmentioning
confidence: 99%